Ultrasound features of immature ovarian teratomas: Case series and review of literature. (May 2020) - Abdullahi Idle, S; Hayes, K; Ross, JA
Introduction: Immature ovarian teratomas are rare but account for 10–20% of ovarian cancers in women under the age of 20 years. This study aimed to characterise immature ovarian teratomas using grey-scale and Doppler ultrasonography and review the literature to refine the diagnosis of immature ovarian teratomas. Methods: Patients with a confirmed histological diagnosis of immature ovarian teratoma from years 2006–2018, who had undergone a transvaginal ultrasound at two large teaching hospitals, were identified. The imaging was retrieved from the centres clinical databases. Ultrasound scans were performed by experienced ultrasound examiners and described according to International Ovarian Tumour Analysis criteria. Results: Eight patients were identified in total with a mean age of 26 years (range 13–35). Half of the patients had a past history of a mature ovarian teratoma (3 ipsilateral, 1 contralateral). The cysts were generally large (median 115 mm), fast growing unilateral lesions with a single, peripheral predominantly solid component arising from the cyst wall. The solid component was hyperechoic with multiple foci of fibrosis and numerous small cysts. The cystic component typically formed less than 75% of the lesion and the cyst fluid was of low-level echogenicity. Subjective assessment of vascularity of the solid part of the tumours varied between scores of 1 and 2. Tumour markers showed a raised serum a-fetoprotein level in 42% of these patients. Conclusion: Although there were no ultrasound features that were pathognomonic of immature teratoma, the diagnosis should be suspected in a young woman with a large ovarian cyst with a fibrotic, microcystic solid component, particularly if she has a past history of a dermoid cyst.